Development and Validation of A Stability-Indicating Mekc Method for Determination of Flucloxacillin Sodium in Capsules - Masquio Fiorentino, Flavia Angelica [UNESP]; Sangoi, Maximiliano da Silva; Steppe, Martin; Salgado, Hérida Regina Nunes [UNESP] (Bentham Science Publ Ltd, 2014)
Flucloxacillin (FLU) is a semi-synthetic penicillin active against Gram-positive bacteria such as streptococci and penicilinase-producing staphylococci, including methicillin-susceptible S. aureus. A simple, rapid and reproducible stability-indicating micellar electrokinetic chromatography (MEKC) method was developed and validated for analysis of flucloxacillin sodium in capsules, using nimesulide as internal standard. The MEKC method was performed on a fused-silica capillary (50 mu m id; effective length of 40 cm). The background electrolyte consists of 50 mM borate and 80 mM anionic surfactant SDS quantities at pH 8.5. The separation was achieved at 20 kV applied voltage and 27.5 degrees C. The injection was performed using the hydrodinamic mode at 50 mbar for 4s, with detection at 210 nm. The method was linear in the range of 20-100 mu g mL(-1) (r = 0.9996) with adequate results for the precision (<= 1.60%) and accuracy (99.45%). The specificity and stability-indicating capability were demonstrated through forced degradation studies and with placebo solution, which showed that there is no interference of the excipients. LOD and LOQ were 3.20 and 9.70 mu g mL(-1), respectively. The method proved to be robust by a fractional factorial design evaluation. The method was successfully applied for the drug analysis and the results were compared to liquid chromatographic method, showing non-significant difference (p > 0.005). The proposed method might be applied in routine quality control in the pharmaceutical industries.
Keywords: Capsules; flucloxacillin sodium; MEKC method; penicillin; quality control; validation